Studi Good Corporate Governance dan kinerja saham perusahaan publik pada sektor manufaktur di Indonesia - Indhira Putri; Iramani Iramani (STIE Perbanas Surabaya, 2017)
This study aimed to examine the effect of Good Corporate Governance on manufac-turing companies. The researchers used the boards of the commissioner, managerial ownership, independent commissioner, and foreign ownership as Good Corporate Governance’s proxy on the performance of the stock. The independent variables con-sist of the boards of the commissioner, managerial ownership, independent commis-sioner, and foreign ownership. The performance of stock is used by using stock re-turn as measurement and dependent variable. The sample consists of manufacturing companies of the period of 2010-201. The hypothesis was tested by using multiple regressions linear. Simultaneously, the boards of commissioners, managerial owner-ship, independent commissioner, and foreign ownership significantly affect the per-formance of the stock. Partially, the boards of commissioner negative significantly affect the performance of the stock. In addition, the managerial ownership and inde-pendent commissioner do not significantly affect the performance of the stock. Yet, the foreign ownership positively and significantly affects the performance of the stock.